Later Permian acritarchs from Meishan (SE China) in the context of Permian palaeobiogeography and palaeoecology - Li, Jun (李军); Cao, CQ (曹长群); Servais, T; Zhu, YH (祝幼华) (E SCHWEIZERBARTSCHE VERLAGS, 2004)
New palynological observations on the Upper Permian of the stratotype area of the Permian/Triassic boundary Meishan, Zhejiang Province, SE China, reveal the presence of rich, but poorly diversified acritarch assemblages, dominated by the Micrhystridium-Veryhachium complex. The palynological assemblage also includes few pollen and spores, scolecodonts, foraminiferal linings and sporadic specimens of Reduviasporonites, a palynomorph that was commonly considered to be a fungal organism, but that is currently attributed to the algae. Our observations indicate the occurrence of an acritarch assemblage typical for Permian offshore environments, but do not provide evidence for a "fungal spike" that may reflect saprophytic activity related to dead vegetation formed during the extinction event of the end-Permian.